Split‐Ugi Reaction with Chiral Compounds: Synthesis of Piperazine‐ and Bispidine‐Based Peptidomimetics. Issue 4 (April 2016) - Stucchi, Mattia; Lesma, Giordano
Abstract : A simple, one‐step, stereoconservative synthesis of diamine‐based peptidomimetics is described, by split‐ Ugi multicomponent reaction, involving chiral N‐protected amino acids and α ‐substituted isocyanoacetate. In particular, piperazine and bispidine (3, 7‐diazabicyclo[3.3.1]nonane) are exploited as diamine components, bispidine being the first example of a sterically demanding bicyclic system employed in a split‐ Ugi reaction. Abstract :